2003
DOI: 10.1002/cncr.11307
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with irinotecan and protein kinase C inhibitors in malignant glioma

Abstract: The topoisomerase-I inhibitor irinotecan (CPT-11) is currently used in Phase I/II trials for the treatment of patients with recurrent malignant gliomas. Protein kinase C (PKC) inhibitors such as high-dose tamoxifen and hypericin also have been used in the treatment of malignant gliomas. The current study examined the role of PKC inhibitors as chemosensitizers for CPT-11 and their proposed mechanism of action. Two glioma cell lines (A-172 and U-87) and one primary glioma cell culture (LA-567) were used.Prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Due to its extremely short half-life, SN-38, the active metabolite of CPT-11, cannot be directly administrated in vivo; therefore, we opted to perform this study using CPT-11 both in vitro and in vivo. Moreover, it has been already shown that cancer cell lines, including glioma cell lines, express carboxylesterase activity and are able to convert CPT-11 into SN-38 (19,20). We believe that the use of CPT-11 in both in vitro and in vivo makes this study more internally consistent than using separate compounds in both tested scenarios.…”
Section: Discussionmentioning
confidence: 72%
“…Due to its extremely short half-life, SN-38, the active metabolite of CPT-11, cannot be directly administrated in vivo; therefore, we opted to perform this study using CPT-11 both in vitro and in vivo. Moreover, it has been already shown that cancer cell lines, including glioma cell lines, express carboxylesterase activity and are able to convert CPT-11 into SN-38 (19,20). We believe that the use of CPT-11 in both in vitro and in vivo makes this study more internally consistent than using separate compounds in both tested scenarios.…”
Section: Discussionmentioning
confidence: 72%
“…In studies, SN-38 has led to decreased concentration of the antiapoptotic protein Bcl-2 and increased expression of the proapoptotic protein Bax. [25][26][27] Resistance to irinotecan and SN-38 is likely mediated by production of IL-1 beta, with activation of NF-kB, a key transcriptional factor that inhibits the apoptotic response. 28,29 SN-38 is further metabolized in the liver to an inactive metabolite, SN-38 glucuronide.…”
Section: Irinotecan: a New Therapeutic Optionmentioning
confidence: 99%
“…24 Glioma cells can convert irinotecan to SN-38 directly. 25 Increased SN-38 concentrations induce cytotoxic changes morphologically, decrease proliferation, and increase cytotoxicity. 25 The mechanism of cytotoxicity is apoptosis.…”
Section: Irinotecan: a New Therapeutic Optionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently there have been a number of reports demonstrating synergistic actions of topo I inhibitors and PKC inhibitors suggesting a potentially useful drug combination [40][41][42] .…”
Section: Karenitecin Treatment Alters the Levels Of Pkcmentioning
confidence: 99%